Lost in Adaptation: The Case for The 'Great' The Great Gatsby. - Ucar, Asya Sakine (ESSE Messenger)
Since its publication, F. Scott Fitzgerald's famous novel The Great Gatsby has been adapted several times, each one offering a distinct representation. The adaptations renew public fascination with Fitzgerald, his fiction, Jazz age fashion and music but also encourage viewers to reconsider their own conceptions of enigmatic Gatsby. But is the popularity of the novel and even its high reputation among literary academics a measure of its greatness? Despite the popularity of 1926, 1949, 1974 and 2013 films, critics maintain that the nuances of the novel are lost in the process of adaptation and even question whether the novel should be represented in another medium paving the way to put an effort of answering why the 'great' Gatsby never makes a great movie.